2022
DOI: 10.3390/nu15010014
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Intake and Risk of Prostate Cancer: A Meta-Analysis

Abstract: Vitamin E is a group of antioxidative tocopherols and tocotrienols that play a potential role in chemoprevention. Studies investigating the association between vitamin E and prostate cancer risk have been conflicting. We identified observational and interventional studies examining the association between vitamin E intake and prostate cancer risk from PubMed, EMBASE and the Cochrane Library. A random-effects model was used to perform a meta-analysis and estimate relative risks (RRs) and the corresponding 95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…As cirrhotic subjects were excluded from this study, causing a lack further evidence in this specific subset of patients, current guidelines do not recommend vitamin E supplementation to cirrhotic patients with obesity, even when dysmetabolic liver disease is present [177]. This caution is justified by the fact that vitamin E toxicity can cause major bleeding events, whereas the possible association between vitamin E supplementation and an increased risk of prostate cancer has not been confirmed by a recent metanalysis [227]. Few data are available to evaluate the effects of antioxidant supplementation in sarcopenia, with overall inconsistent evidence [228].…”
Section: Vitamin E (Tocopherol)mentioning
confidence: 98%
“…As cirrhotic subjects were excluded from this study, causing a lack further evidence in this specific subset of patients, current guidelines do not recommend vitamin E supplementation to cirrhotic patients with obesity, even when dysmetabolic liver disease is present [177]. This caution is justified by the fact that vitamin E toxicity can cause major bleeding events, whereas the possible association between vitamin E supplementation and an increased risk of prostate cancer has not been confirmed by a recent metanalysis [227]. Few data are available to evaluate the effects of antioxidant supplementation in sarcopenia, with overall inconsistent evidence [228].…”
Section: Vitamin E (Tocopherol)mentioning
confidence: 98%
“…Studies investigating the application of vitamin E as a cancer-fighting supplement in vivo have prioritized utilizing the δ- and γ-tocopherol forms—likely due to recent findings suggesting that α-tocopherol is not as effective as these other tocopherols as a preventative agent and antioxidant [ 127 , 128 , 129 , 130 , 131 , 132 ]. One such experiment investigated the ability of a γ-tocopherol-rich mixture of tocopherols (γ-TmT; 57% γ-tocopherol, 24% δ-tocopherol, 13% α-tocopherol and 1.5% β-tocopherol) to block tumorigenesis in mice directly exposed to the carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) with or without the carcinogen benzo[ a ]pyrene (B[ a ]P).…”
Section: Vitamin Ementioning
confidence: 99%
“…Researchers in this study found no influence of γ-tocopherol in preventing prostate tumor growth when compared to the control population [ 137 ]. This apparent inability for vitamin E to impact tumorigenesis of prostate cancer in rats may be related to recent findings that suggest vitamin E supplementation does not improve the risk of developing prostate cancer and may in fact actually increase the risk of prostate cancer in humans via the aforementioned increase in cytochrome family activity [ 126 , 129 , 130 , 138 , 139 ].…”
Section: Vitamin Ementioning
confidence: 99%
See 2 more Smart Citations